PENGARUH GELOMBANG ULTRA LOW FREQUENCY (ULF) DALAM PERILAKU CACING TANAH DI SOLO DAN KLATEN - I Putu Pudja (Stasiun Pemantau Atmosfer Global Bukit Kototabang, 2023)
Deformed rocks emit Ultra Low Frequency (ULF) waves and affect the earth's magnetic field. So that ULF gives anomalies to the surroundings. ULF emissions also influence animal behavior. Changes in earthworm behavior in Solo and Klaten on 18 April 2020 coincided with the peak lead time period of deformation calculated by the ULF anomaly on the BMKG magnetograph in Yogyakarta. The location of the discharge area of ​​earthworms is in the deformation coverage area in accordance with the purpose of the interference in the results of the analysis of the magnetograph records. The ULF anomaly in Indonesia is being developed for earthquake prediction, as well as the phenomenon of animal behavior being widely studied for earthquake prediction. Collaboration on animal behavior research, including earthworms and ULF research, provides hope for the development of earthquake predictions in Indonesia.